De-labelling severe asthma diagnosis: the challenge of DIPNECH. Issue 1 (7th February 2021) - Hurabielle, Caroline; Taillé, Camille; Prévot, Grégoire; Russier, Maud; Didier, Alain; Girodet, Pierre-Olivier; Colombat, Magali; Mazières, Julien; Guilleminault, Laurent
Diffuse idiopathic pulmonary neuroendocrine cell hyperplasia (DIPNECH) is a rare pulmonary disease characterised by neuroendocrine cell hyperplasia within the bronchial epithelium [1]. The clinical presentation is characterised by nonspecific respiratory symptoms such as chronic cough, dyspnoea and bronchospasm. Given the rarity of the disease and the low specificity of symptoms, the diagnosis of DIPNECH is challenging and the time between symptom onset and diagnosis is long [1]. DIPNECH comprises a generalised proliferation of scattered neuroendocrine cells, small nodules (neuroendocrine bodies) or a linear proliferation of pulmonary neuroendocrine cells. It has been suggested that DIPNECH may mimic [2] or precede [3] asthma. The role of products of neuroendocrine cells such as substance P, which contribute to eosinophil migration, has been suggested to explain asthma symptoms in DIPNECH [3]. However, the characteristics of patients with DIPNECH who have symptoms suggestive of asthma have never been described. The aim of our study was to determine whether patients diagnosed with DIPNECH and initially referred for severe asthma management had specific characteristics. DIPNECH is a differential diagnosis of severe asthma with no specific biomarkers. Chronic cough and multiple nodules on CT should prompt clinicians to consider this diagnosis. Differentiating DIPNECH from severe asthma remains crucial. https://bit.ly/3mmFbQn